On-line extraction and determination of residual sulfathiazole in pharmaceutical wastewater with molecularly imprinted polymers in a packed cartridge coupled with high-performance liquid chromatography. Issue 20 (11th May 2017) - Zazouli, Mohammad Ali; Akbari-adergani, Behrouz; Javanbakht, Mehran; Moein, Mohammad Mahdi
Abstract : A new, rapid and sensitive on-line extraction and determination technique was developed with molecularly imprinted polymers (MIPs) in a packed cartridge. Abstract : A new, rapid and sensitive on-line extraction and determination technique was developed with molecularly imprinted polymers (MIPs) in a packed cartridge. An artificial selective polymeric sorbents packed in a polyethylene cartridge were employed for the separation of sulfathiazole residue. The packing particles were synthesized using methacrylic acid as a functional monomer, ethylene glycol dimethacrylate as a cross-linker agent, sulfathiazole as a target template molecule and azobisisobutyronitrile as an initiator. The optimal conditions for designing these sorbents were as follows: conditioning using water with pH = 3.0, loading the sample under mild basic aqueous conditions, cleanup using 2 × 2 mL acetonitrile and elution with 3.0 mL 20 mM ammonium acetate : acetonitrile (75 : 25 v/v, pH = 3.0). In this system, an aliquot of extracted template was injected to the HPLC analytical column with acetonitrile : water (75 : 25 v/v) and water (pH adjusted to 3.0 with H3 PO4 ) as the mobile phases in a gradient elution program. The selectivity of the MIPs in the packed cartridge was evaluated by checking several substances with molecular structures similar to that of the template. The results revealed a recovery of more than 92% along with a limit of detection and limit of quantification of 0.05 and 0.16 ng mL −1, respectively, for the on-line determination of sulfathiazole in pharmaceutical wastewater samples.